A Case Report on Chikungunya Virus-Associated Encephalomyelitis - Harsh Khatri; Heli Shah; Dhara Roy; Kaushalendra Mani Tripathi (Case Reports in Infectious Diseases)
Chikungunya is a rerising alphavirus infection that has resulted from enhanced vector competence. Alphaviruses are divided into arthritogenic viruses (old world) and encephalitogenic viruses (new world) including equine encephalitis viruses. Chikungunya is a dengue-like illness characterized by acute febrile polyarthralgia, arthritis, malaise, body ache, rash, headache, and nausea. The illness is self-limiting. The neurological manifestations are uncommon and incorporate meningoencephalitis, myelitis, Guillain–Barre syndrome, cranial nerve palsies, myelopathy, and neuropathy; MRI abnormalities in patients with encephalopathy from India have been reported in the form of multiple punctuate white matter lesions that are more prominent on diffusion-weighted MRI than on T2 or T1. Here, we present an intriguing case of chikungunya encephalomyelitis who presented to our tertiary care hospital with quadriparesis and urinary retention. He was treated with 5 doses of intravenous immunoglobulin along with supportive care with which he showed partial recovery.